1/2x - 2/3y = -6
6(1/2x) - 6(2/3y) = 6(-6)
6/2x - 12/3y = - 36
3x - 4y = - 36
3(0) - 4y = - 36
0 - 4y = - 36
- 4y/-4 = - 36/-4
y = 9
The y intercept is 9 when x = 0
- - - - - -s-
2006-10-25 08:11:23
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
Y=9
2006-10-25 12:53:49
·
answer #2
·
answered by HI! 2
·
0⤊
0⤋
If you want to solve for y, first you have to isolate it. Do this by adding -1/2x to each side (or, you could think of it as subtracting 1/2x from each side) of the equation.
-2/3y = - 6 -1/2x
Divide both sides by -2/3, which is the same as multiplying by -3/2. To do this, multiply each term by -3/2. (Note: watch the sign changes here.)
y = -3/2(-6 - 1/2x) = (-3/2 * -6) - ((-3/2) * 1/2x )
= 18/2 - (-3/4x) = 9 + 3/4x
Simplifying this result by externalizing the common factor 3, we have:
y = 3 (3 + 1/4x)
You find your y intercept by plugging in a value for x and seeing what the resulting number is. The y intercept when x = 0 is:
y = 3( 3 + 1/4 * 0) = 3 (3 + 0) = 9.
By solving y for successive values of x, you can plot a graph of (x,y) coordinate pairs. Try it yourself on graph paper for positive and negative values of x.
2006-10-25 12:30:36
·
answer #3
·
answered by geekgrrl 1
·
0⤊
0⤋
you have to transform th equation in terms of y:
1/2x+6=2/3y
then you multiply both sides of the equation by 3/2 therfore:
3/4x+9=y
the y intercept occus when x=0 therefore you put x=0 in the equation and get 3/4(0)+9=y
3/4 time 0 os equal to zero therforew the y intercept is y=9
2006-10-25 12:22:23
·
answer #4
·
answered by haris 1
·
0⤊
0⤋
isolate "Y" ... in the form of Y = mX + b .... b = intercept
1/2x -2/3Y = -6 (multiply all by 6 to remove denominators)
3x - 4y = -36 isolate y
3x + 36 = 4y divide by 4
3/4 x + 9 = Y intercept = 9
2006-10-25 12:28:03
·
answer #5
·
answered by Brian D 5
·
0⤊
0⤋
you transform your equation in form y=mx+b
the y-intercept will be your b
1/2x + 6 = 2/3y
multiply by 3/2
3/4x - 9 = y
then your y-intercept is 9
Please best answer
2006-10-25 12:12:28
·
answer #6
·
answered by Melia 2
·
1⤊
0⤋
Start by multiplying every term by the common denominator of 6 to get rid of the fractions.
3x - 4y = -36 Now solve for y.
-4y = 3x - 36
y = -3/4 x + 9
Your equation is now in slope intercept form, y = mx + b, where m is the slope and b is the y intercept. So the y intercept is (0,9).
2006-10-25 12:12:40
·
answer #7
·
answered by PatsyBee 4
·
1⤊
0⤋
A line's intercept is where the line crosses the x or y axis
and since you ask for the y incept it where the line crosses the y axis .
Lets look at the equation Do ypou see where it says 2/3y ? this is where the line crosses the y axis so this is the y intercept ?
2006-10-25 12:15:09
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
.... u get d following equations..
y/2-2x/3=-6xy
3y-4x=-36xy
4x-36xy-3y=0
to get the y intercept x=0
hence the y intercept is zero....
2006-10-25 12:15:13
·
answer #9
·
answered by the_great_one 1
·
0⤊
0⤋
1/2*x-2/3*y=-6
divide the eqn by -6
x/-12+y/9=1
Now we have it in the form
x/a+y/b=1
y intercept=b=9
2006-10-25 12:16:33
·
answer #10
·
answered by openpsychy 6
·
0⤊
0⤋